Inter-Annual Variability of Winter Precipitation Over Nepal Coupled With Ocean-Atmospheric Patterns During 1987–2015 - Hamal, Kalpana; Sharma, Shankar; Baniya, Binod; Khadka, Nitesh; Zhou, Xu (Frontiers in Earth Science, 2020)
Nepal is a mountainous country located on the southern slope of the central Himalayas, where the winter season contributes ∼3% of the total annual rainfall. This study sought to investigate the inter-annual variability and associated ocean-atmospheric pattern with winter precipitation during 1987–2015. A high-resolution APHRODITE and ERA5 reanalysis datasets are used to study the Empirical Orthogonal Function (EOF), Wavelet, Composites, and Correlation analysis, respectively. The results show that the leading EOF mode captures 53.2% of the total variance, exhibiting a single mode of variability. Wavelet analysis determined 2 to 2.6 years of the significant power spectrum. The time-series of winter precipitation anomalies revealed the years 1996, 1998, 2000, 2005, 2007, and 2008 as precipitation deficit years which is supported by negative precipitation anomalies with positive outgoing longwave radiation (OLR) and vertical velocity. These phenomena are converse for wet events during the years 1988, 1995, 1997, 2002, 2012, and 2014. Furthermore, the wet (dry) years exhibit moisture convergence (divergence) with strong southwesterly (northwesterly) wind anomalies. In the wave train of westerly flow, the cyclonic and anticyclonic circulation in northern India affects the moisture transport in wet and dry years, respectively. In excess precipitation years, Surface Air Temperature (SAT) over entire northern India and adjoining Nepal and Tibetan Plateau (TP) regions have a colder temperature than in deficit precipitation years. The correlation suggests the instance of Indian Ocean Basin Mode (IOBM) and NINO3.4 impacts on the inter-annual variability of the winter precipitation. Moreover, the warming and cooling over the Indo-Pacific regions affect the Walker and Hadley circulation bringing above and below-normal precipitation, respectively, over Nepal. The observed changes in the dry and wet years during winter are useful for disaster preparedness and the planning and monitoring of water resources and agriculture.